THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN MUSICAL CULTURE CLASSES - S.M. Askarova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article talks about the use of information and communication technologies in the classroom, its purposes, capabilities and advantages of using this technology.